The Relationship Between Knowledge and Reproductive Hygiene Practices Among Adolescent Girls at Al Fatih Islamic Boarding School, Sintang, Indonesia: A Cross-Sectional Study - Hearty Efifania Ose Payon; Khairulisni Saniati; Dian Ika Pratiwi; Ngaisah Tri rahayu (Jurnal Kebidanan Manna, 2026)
Background: Reproductive hygiene is an essential aspect of adolescent health, particularly among female adolescents living in boarding school environments. Limited knowledge regarding reproductive health may contribute to poor hygiene practices, increasing the risk of reproductive tract infections and other health problems. Objective: This study aimed to analyze the association between knowledge and reproductive hygiene practices among female adolescents at Al Fatih Islamic Boarding School, Sintang. Methods: This study was an analytical observational study with a cross-sectional design. A sample of 109 respondents from a total population of 150 students was selected using the Slovin formula and simple random sampling technique. Knowledge was measured using a questionnaire with true/false items, while hygiene behavior was assessed using a behavioral questionnaire. Data analysis was performed using univariate analysis and the Chi-square test with a significance level of p < 0.05. Results: The majority of respondents had good knowledge (56.0%) and good reproductive hygiene practices (65.1%). The Chi-square test showed a statistically significant association between knowledge and reproductive hygiene practices (p < 0.001). Respondents with higher knowledge were more likely to demonstrate good reproductive hygiene practices compared to those with moderate and poor knowledge. Conclusion: There is a significant association between knowledge and reproductive hygiene practices among female adolescents at Al Fatih Islamic Boarding School, Sintang. Strengthening reproductive health education programs is essential to improve adolescents’ hygiene behavior.